Panduan Penggunaan Pupuk Organik Berbasis Android - Marlina; Olivia Angelytha De Buck (Fakultas Teknik Universitas Muhammadiyah Parepare, 2025)
The lack of understanding of the farming community in making quality and affordable organic fertilizer is a problem among the community. The aim of the research is to create an application to provide the public with an understanding of the procedures for making and using organic fertilizer. The research method used was experimental, conducted through a literature study. Located on Lia'e Jl. Lappa Anging in Parepare City, research time was three months. A tool that helps in analyzing and designing applications using the Kotlin programming language with Android Studio tools. The resulting application, called Agrismart App, has several menus that show two main menus, namely: a catalog menu containing text on tips for making organic fertilizer, tools and materials, and the use of organic fertilizer; and a video menu containing procedures for making eleven types of organic fertilizer.